Effect of air addition to the air electrode on the stability and efficiency of carbon dioxide electrolysis by solid oxide cells. (8th July 2022) - Wu, Anqi; Li, Chaolei; Han, Beibei; Hanson, Svenja; Guan, Wanbing; Singhal, Subhash C.
Abstract: In this study, the effect of air addition to the air electrode on the long-term stability and efficiency of solid oxide cells for CO2 electrolysis, with 23.8% CO as protective gas in the fuel electrode, has been investigated. The results show that without continuous purging of the air in the air electrode (Cell-1), the degradation rate was 8.37%/kh in the 1070 h electrolysis process, while with 5 L/min air supplied to the air electrode (Cell-2), the degradation rate was 24.41%/kh. Impedance analysis indicates that the degradation of Cell-1 was mainly because of the increase in O 2− exchange polarization impedance, while the degradation of Cell-2 was caused mainly by the variation of ohmic impedance. The microstructural characterization indicated a decrease in active Ni in the fuel electrode in both Cell-1 and Cell-2, but the degree of nickel loss depended on the test time. At the outlet of the Cell-2, the appearance of carbon further explains the faster degradation rate, although the carbon deposition was not directly caused by the introduction of air into the air electrode. Energy spectral analysis shows that the air electrode in Cell-1 generated Sr rich phases, which indicates that the absence of air in the air electrode in the electrolysis process indeed causes more serious microstructure damage. The energy conversion efficiency could exceed 86% if the energy consumed for heating the air is ignored. This work provides a scenario for the application of solid oxide cells for CO2 electrolysis without air purging in the air electrode. Highlights: 1070 h of CO2 electrolysis was conducted with no gas in air electrode. Energy conversion efficiency reached more than 86% at −200 mA cm −2 and 1.216 V. The voltage degradation rate was 8.37%/kh with no gas in air electrode. The loss of Ni (more than 3%) dominates the degradation of fuel electrode. The formation of Sr rich phase dominates the deterioration of air electrode.